2007
DOI: 10.3357/asem.2054.2007
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration Effects on Manual Performance With Isometric and Displacement Joysticks

Abstract: Exaggerated force production in +3 Gz is not overcome by task practice in normal G, as opposed to task practice in +3 Gz. This might be an indication that pilot training should contain extended practice of force production during phases of increased gravity (+Gz) to avoid motor deficits during flight maneuvers inducing +Gz. Furthermore, the control of isometric and regular joysticks seems to be based on partly distinct neural mechanisms, with different +Gz dependence. Thus, against the background of motor perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
3
10
0
1
Order By: Relevance
“…SigniWcant eVects of Force emerged for Initial Force (F(2,22) = 4.32; P < 0.05), Peak Force (F(2,22) = 23.86; P < 0.001) and End force (F(2,22) = 24.02; P < 0.001); this was expected, since produced force magnitude increased with target force magnitude. ANOVA also revealed signiWcant eVects of Direction on Peak Force (F(7, 77) = 2.24, P < 0.05), and of Force*Direction on Initial Force (F(14,154) = 2.51; P < 0.01), Peak Force (F(14,154) = 37.86; P < 0.001) and End Force (F(14,154) = 34.81; P < 0.001); this conWrms earlier Wndings, which had been attributed to biomechanical anisotropy (Sand et al 2003;Girgenrath et al 2005;Guardiera et al 2007a).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…SigniWcant eVects of Force emerged for Initial Force (F(2,22) = 4.32; P < 0.05), Peak Force (F(2,22) = 23.86; P < 0.001) and End force (F(2,22) = 24.02; P < 0.001); this was expected, since produced force magnitude increased with target force magnitude. ANOVA also revealed signiWcant eVects of Direction on Peak Force (F(7, 77) = 2.24, P < 0.05), and of Force*Direction on Initial Force (F(14,154) = 2.51; P < 0.01), Peak Force (F(14,154) = 37.86; P < 0.001) and End Force (F(14,154) = 34.81; P < 0.001); this conWrms earlier Wndings, which had been attributed to biomechanical anisotropy (Sand et al 2003;Girgenrath et al 2005;Guardiera et al 2007a).…”
Section: Resultssupporting
confidence: 86%
“…We found peak force to increase under water by about 24%, which is comparable to the increase of 20% under visual Weld motion (Dalecki et al 2009), 30% during centrifugation (Guardiera et al 2007a) and 16% during weightlessness (Mierau et al 2008). In contrast, initial force increased under water only by 3%, which is non-signiWcant and substantially smaller than the increase of 42% under visual Weld motion (Dalecki et al 2009), 140% during centrifugation (Guardiera et al 2007a) and 20% during weightlessness (Mierau et al 2008). This pattern of Wndings support the hypothesis outlined in the Introduction: initial forces increase during visual Weld motion, centrifugation and weightlessness probably because of vestibular stimulation, but not under water, where such stimulation is absent; in contrast, peak forces increase in water immersion as well, since all scenarios seem to degrade proprioceptive feedback.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This is further supported by the good correlations (similar to 1 g conditions) between increments of the grip force and the load force in hypergravity and by the synchronization of grip force with load force that did not change across the two gravitational conditions. These results are also similar to the results of a previous experiment in which isometric force production was exaggerated under hypergravity, whereas hand displacements were similar to the normal gravity condition (Guardiera et al 2007). In the context of Bayesian integration, these and our results are compatible with the fact that visual feedback-providing good estimates of the effector's position and velocity-comes into play in the context of movement control, whereas force estimation is mostly based on prior experience and on proprioceptive signals, the latter being directly influenced by the force background.…”
Section: Discussionsupporting
confidence: 82%
“…W E HAVE PREVIOUSLY shown that subjects exposed to three times the normal terrestrial acceleration ( 1 3 G z ) are impaired in their ability to produce fi nely graded manual forces: control subjects as well as G z -experienced fi ghter pilots produce substantially exaggerated peak responses ( 1 30%) in 1 3 G z ( 2,8,9,13 ). This impairment cannot be attributed to the direct mechanical effects of 1 3 G z , faulty proprioceptive feedback, or a higher cognitive load ( 5 ), but it may be explained by the effects of changed vestibular activity on voluntary motor commands ( 4 ).…”
mentioning
confidence: 99%